1975
DOI: 10.1080/09670877509411384
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes of Pineapple: A Review

Abstract: lnsrirut Francais de Recherches FruitGres Ourre Mer (I. F.A. CJ, B. P. 1740 Abidjan, Ivory Coast.Summary. Pineapple growing i s very important in the economy of many tropical countries, but nematodes are a very serious problem in this crop. Among the many phytophagous species found in the root zone of pineapples, Meloidogyne spp., Prarylenchus spp. and Rotylenchulus reniformis (Linford and Oliveira) are particularly important.In fact, these species can reduce the yields by more than 40% for the first crop and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Pratylenchus brachyurus, a cosmopolitan species, appears as the predominant species on yam in Nigeria and Ghana, which is in agreement with other studies that have reported P. brachyurus from yam in Nigeria and West Africa ( Luc and de Guiran, 1960 ; Unny and Jerath, 1965 ; Caveness, 1967 ; Bridge, 1972, 1973 ). In this region, the polyphagous P. brachyurus has also been recorded as a pest of numerous crops ( Miège, 1957 ; Luc and de Guiran, 1960 ; Bridge, 1973 ; Egunjobi, 1974 ; Egunjobi and Larinde, 1975 ; Guerout, 1975 ; Coyne et al, 1999 ; Castillo and Vovlas, 2007 ), including an interception from Colocasia sp. (another tuber crop) from Nigeria to China ( Zhao et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pratylenchus brachyurus, a cosmopolitan species, appears as the predominant species on yam in Nigeria and Ghana, which is in agreement with other studies that have reported P. brachyurus from yam in Nigeria and West Africa ( Luc and de Guiran, 1960 ; Unny and Jerath, 1965 ; Caveness, 1967 ; Bridge, 1972, 1973 ). In this region, the polyphagous P. brachyurus has also been recorded as a pest of numerous crops ( Miège, 1957 ; Luc and de Guiran, 1960 ; Bridge, 1973 ; Egunjobi, 1974 ; Egunjobi and Larinde, 1975 ; Guerout, 1975 ; Coyne et al, 1999 ; Castillo and Vovlas, 2007 ), including an interception from Colocasia sp. (another tuber crop) from Nigeria to China ( Zhao et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…(another tuber crop) from Nigeria to China ( Zhao et al, 2011 ). Also, it is known to affect plant growth and the yield of crops in West Africa, for instance on pineapple ( Guerout, 1975 ) and cassava ( De Guiran, 1965 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several species of parasitic nematodes have been reported on pineapple such as root-knot (Meloidogyne javanica and Meloidogyne incognita), lesion (Pratylenchus brachyurus) and reniform (Rotylenchulus reniformis) (Guerout, 1975;Rabie, 2017). The importance of nematodes that are responsible for the losses in pineapple farms have been recorded in Costa Rica (Araya, 2017b), Peru (Vera Obando et al, 2017, France (Soler et al, 2021), Africa (Coyne et al, 2018) and Nigeria (Daramola et al, 2013).…”
Section: Causal Parasitementioning
confidence: 99%
“…It was described for the first time in pineapple roots by Godfrey (1929) in Hawaii. This nematode penetrates the elongation zone of roots and develops in the cortical tissue and vascular cylinder (Guérout 1975). Secondary roots can then be destroyed by nematode infestation giving a root system that is essentially composed of primary roots (Caswell et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in fruit yield can be in the region of 30 to 35% and the number of suckers may be reduced to 80% (Lacoeuilhe andGuérout 1976,Keetch 1982). P brachyurus has a high impact in the Ivory Coast (Guérout 1975), because pineapple is often grown in soil with a pH adapted to nematode proliferation (pH 5 to 5.5) (Sarah 1991).…”
Section: Introductionmentioning
confidence: 99%